Formulation of Java Acid Leaves (Tamarindus indica L.) Etanol Extract Salep Devices With Absorption, Hydrocarbon, Water Solution and Water Washable Basis (O/W Emulsion) - Kurniaty, Rina; Sukma Ratmelya, Dara (Universitas Negeri Medan, 2025)
Tamarind leaves have flavonoid, tannin and saponin compounds, which can be used as antibacterials. Research has been conducted on the formulation of ointment preparations from tamarind leaf ethanol extract (Tamarindus indica L.) using a variety of ointment bases, namely absorption, hydrocarbon, water soluble and washable with water (O/W emulsions). This study aims to determine the physical stability and the appropriate type of ointment base of tamarind leaf ethanol extract ointment preparation. The extraction process in this study used maceration method with 70% ethanol solvent. The formalized preparation was evaluated for physical stability for 10 days at 4°C and 25°C alternately every 24 hours (1 cycle). The evaluation included organoleptic test, pH, homogeneity and spreadability. Absorption ointment made from ethanol extract of tamarind leaves is light brown in color, smells typical of tamarind, homogeneous, has a pH of 4 and has a spreadability of 5 cm. Hydrocarbon ointment is dark brown in color, smells typical of tamarind, homogeneous, has a pH of 3 and has a spreadability of 3.95 cm. Water soluble ointment with ethanol extract of tamarind leaves is dark brown in color, smells typical of tamarind, homogeneous, has a pH of 3 and has a spreadability of 5.3-5.5 cm. Water washable ointment (O/W emulsion) is light brown in color, smells typical of tamarind, homogeneous, has a pH of 4, and has a spreadability of 3.93 cm. Based on the test results in this study, it can be concluded that the formulation of ethanol leaf extract preparation.